Use of fully covered self-expandable metal stents for benign esophageal disorders in children - Lange, Bettina; Kubiak, Rainer; Wessel, Lucas; Kähler, Georg (Journal of laparoendoscopic & advanced surgical techniques, 2015)
Purpose: There is a lack of experience with fully covered self-expandable metal stents (SEMSs) for benign esophageal disorders in children. Patients and Methods: Eleven children (six boys, five girls) with a median age of 30.5 months (range, 1 month-11 years) who underwent treatment with SEMSs for a benign esophageal condition between February 2006 and January 2014 were recruited to this retrospective study. Etiologies included esophageal atresia with postoperative stricture (n=4), recurrent fistula (n=1), and/or anastomotic leak (n=1), as well as iatrogenic perforation of the esophagus following endoscopy (n=4) or laparoscopic fundoplication (n=1). As part of an interdisciplinary cooperation patients were jointly managed from the Department of Pediatric Surgery and Central Interdisciplinary Endoscopy at our institution. Results: Median duration of individual stent placement was 29 days (range, 17-91 days). In 4 cases up to four different SEMSs were placed successively over time. There were no complications noted at stent insertion or removal. At follow-up, 6 patients (55%) were successfully treated without further intervention. Two children each (18%) underwent one single dilatation after stent removal and remained well afterward. Three patients (27%) did not improve following stenting and required definite surgery. Minor stent-related complications were noted in 5 cases (45%), including gastroesophageal reflux (n=2), silent stent migration (n=2), and pneumonia (n=1). Conclusions: SEMSs for benign esophageal disorders in children can be used safely and effectively in selected cases, including esophageal anastomotic strictures, esophageal leaks following primary surgery, or perforations postdilatation. An SEMS can be applied either as an emergency procedure or as an adjuvant treatment further to endoscopy or previous surgery. Establishment of a standardized approach in the pediatric population is mandatory.